2020
DOI: 10.3390/foods9111689
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Salmonella Typhimurium by Non-Thermal Plasma Bubbles: Exploring the Key Reactive Species and the Influence of Organic Matter

Abstract: The key reactive species generated by non-thermal plasma bubbles for the inactivation of Salmonella Typhimurium and the effects of organic matter on the inactivation efficacy were investigated. Plasma, which is primarily composed of ozone (O3), was generated by dielectric barrier discharge and injected into a solution (400 mL) as a bubble. The surviving population of S. Typhimurium decreased in proportion to the treatment time, resulting in a 5.29 log reduction after 5 min of treatment. Verification tests to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 38 publications
3
13
0
Order By: Relevance
“…Tiron selectively interacts with and is oxidized by superoxide, allowing its effective removal from the solution (Peskin et al, 1998;Taiwo, 2008). The demonstration of superoxide as a major player in our novel DBDD system is supported by previous research that found superoxide anions and downstream reactive species such as singlet molecular oxygen to be significant contributors to the antimicrobial activity of PAW produced by a dialectic barrier discharge system using plasma generated above the water interface with helium as a feed gas (Xu et al, 2021) and in a bubble system using deionized water (Baek et al, 2020).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Tiron selectively interacts with and is oxidized by superoxide, allowing its effective removal from the solution (Peskin et al, 1998;Taiwo, 2008). The demonstration of superoxide as a major player in our novel DBDD system is supported by previous research that found superoxide anions and downstream reactive species such as singlet molecular oxygen to be significant contributors to the antimicrobial activity of PAW produced by a dialectic barrier discharge system using plasma generated above the water interface with helium as a feed gas (Xu et al, 2021) and in a bubble system using deionized water (Baek et al, 2020).…”
Section: Discussionsupporting
confidence: 62%
“…The energetic collisions of electrons with O 2 molecules (O 2 + e − →2O + e − ) account for the formation of ∙O radicals (Zhou et al, 2020) at 777.2 and 844.6 nm, which were produced by both reactors but in higher concentrations in the BSD reactor (Figure 5). Previous studies of dielectric barrier discharge PAW have similarly observed increasing concentrations of O 3 over the activation period (Zhou, Zhou, et al, 2021) and very low concentrations of NO x (Baek et al, 2020).…”
Section: Discussionmentioning
confidence: 82%
“…Trion selectively interacts with and is oxidized by superoxide, allowing its effective removal from the solution (26,27). Our finding is supported by previous research showing that superoxide anions and downstream reactive species such as singlet molecular oxygen are significant contributors to the antimicrobial activity of PAW produced by dialectic barrier discharge against yeast cells (28) and Salmonella Typhimurium (29).…”
Section: Discussionsupporting
confidence: 90%
“…These fine particles (≤ 1.0 μm) can evaporate within a few milliseconds, becoming virus-containing “droplet nuclei” and spreading over a wide area of air [ 2 ]. The air-passable DFD generator showed electrical characteristics ( Fig 2B ), which can be observed in the general dielectric barrier discharge [ 21 23 ]. The discharge remained stable even when the media aerosols passed through the discharge area.…”
Section: Resultsmentioning
confidence: 99%